2019
DOI: 10.1074/jbc.ra118.006330
|View full text |Cite
|
Sign up to set email alerts
|

The small RbcS-like domains of the β-carboxysome structural protein CcmM bind RubisCO at a site distinct from that binding the RbcS subunit

Abstract: Edited by Norma M. Allewell Carboxysomes are compartments in bacterial cells that promote efficient carbon fixation by sequestering RubisCO and carbonic anhydrase within a protein shell that impedes CO 2 escape. The key to assembling this protein complex is CcmM, a multidomain protein whose C-terminal region is required for RubisCO recruitment. This CcmM region is built as a series of copies (generally 3-5) of a small domain, CcmM S , joined by unstructured linkers. CcmM S domains have weak, but significant, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
51
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 43 publications
3
51
1
1
Order By: Relevance
“…Despite the potential effects caused by YFP fusion, it could suggest the presence of a "storage pool" of carboxysome proteins located in the cytoplasm, which are involved in the biogenesis, maturation and turnover of carboxysomes. The ratio of RbcL/S detected from cell lysates fraction is about 8:5.8 (n = 4) (Supplemental Table 2), in line with previous results (Long et al, 2011) but distinct from the in vitro reconstitution observations (Ryan et al, 2018;Wang et al, 2019).…”
Section: Protein Stoichiometry Of Functional Carboxysomes At the Singsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the potential effects caused by YFP fusion, it could suggest the presence of a "storage pool" of carboxysome proteins located in the cytoplasm, which are involved in the biogenesis, maturation and turnover of carboxysomes. The ratio of RbcL/S detected from cell lysates fraction is about 8:5.8 (n = 4) (Supplemental Table 2), in line with previous results (Long et al, 2011) but distinct from the in vitro reconstitution observations (Ryan et al, 2018;Wang et al, 2019).…”
Section: Protein Stoichiometry Of Functional Carboxysomes At the Singsupporting
confidence: 90%
“…Recent studies indicated that CcmM interacts with Rubisco (RbcL8S8) at distinct sites, without displacing RbcS (Ryan et al, 2018;Wang et al, 2019). Based on the L8S8 ratio and RbcS abundance per carboxysome determined, we estimated that there are approximately 853, 550, 367, and 1507 copies of Rubisco per β-carboxysome under Air/ML, CO2/ML, LL, and HL, respectively ( Figure 6A, Table 1).…”
mentioning
confidence: 88%
“…The SSUL domain shares 54-64 % sequence identity with the three SSUL modules of the CcmM protein (NosM58) and its shorter variant M35 (NosM35) (Long et al, 2010) (Figure 6A and S6A). The SSUL modules of CcmM function as scaffolding proteins to concentrate Rubisco into a dense condensate prior to encapsulation into the β-carboxysome (Ryan et al, 2019;Wang et al, 2019). Thus, it seemed plausible that the SSUL domains recruit NosRca into the Rubisco condensate (Lechno-Yossef et al, 2020).…”
Section: Function Of the Ssul Domains In Carboxysome Organizationmentioning
confidence: 99%
“…To test whether the small subunits of RubisCO are indeed displaced upon binding of CcmM, Ryan et al (8) used native MS and size exclusion chromatography methods to measure the size of the complex formed between isolated CcmM assembly domains and RubisCO. They showed that it was consistent with 1-5 CcmM assembly domains binding to each RubisCO hexadecamer, without the detection of any free RubisCO small subunits, strengthening the contention that CcmM can bind to RubisCO without displacing the small subunits ( Fig.…”
mentioning
confidence: 99%
“…overall binding of the complete CcmM protein, which contains multiple assembly domains joined by short linker regions. To determine if this was indeed the case, Ryan et al (8) used surface plasmon resonance binding assays to measure the binding affinity of CcmM constructs containing either a single assembly domain, two assembly domains joined by a linker, or all four assembly domains. These assays showed that all CcmM constructs bound RubisCO with a similar affinity, in the low micromolar range, confirming that a single CcmM binding domain binds in a fashion similar to the full-length protein and providing one of the first direct measurements of the affinity of RubisCO for one of its binding partners.…”
mentioning
confidence: 99%